Mejoramiento Urbano del Entorno Inmediato del Parque Principal de Floridablanca- Santander (2023)
This urban intervention project was carried out in the municipality of Floridablanca Santander, where an improvement of the immediate surroundings of the main park was proposed. It addressed issues in the public space within a polygon of nine city blocks. Architectural surveys, mobility analysis, public space evaluation, and sustainability assessments were conducted to identify guidelines for mitigating the issues.